Dicyclo-hexyl-ammonium bromide. - Lo, K.M.; Ng, Seik Weng (International Union of Crystallography, 2008)
In the title compound, C(12)H(24)N(+)·Br(-), both cyclo-hexane rings adopt the usual chair conformation. The cation and anion are linked by N-H⋯Br hydrogen bonds into a linear chain running along the c axis.